On the product of inner radii of symmetric nonoverlapping domains - Bakhtin, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
Some results concerning extremal problems for nonoverlapping domains with free poles on the unit circle, known for the simply connected case, are generalized to the case of multiply connected domains.